Load balance based relay selection and spectrum transition joint scheme - Bo HUANG; Xu-ming FANG; Yu CHEN; Gao-yong HUANG (Tongxin xuebao)
For load imbalance or hotspot coverage wireless relay network, an adaptive load balance relay selection and spec-trum transition joint scheme was proposed. An interference capacity of the stations was also proposed, which reflects the in-terference to the surrounding co-channel stations. The interference capacity provides a quantitative interference metric to the surrounding stations on the capacity of the system. When a user requires to access the system, the system chooses a preferred access station and an alternative access station for the user according to the channel quality. If the preferred access station is overloaded and does not have enough resources for the user, the performance between accessing to the alternative station and accessing to the preferred station with spectrum transition from other stations in the same sector were compared, and a better way was choosen to maintain the good system performance. The simulation results show that the spectrum efficiency and blocking probability of the proposed scheme in the center cell are superior to that of the independent relay selection scheme and the independent load balance based spectrum transition scheme, and the average interference capacity of the proposed scheme is the lowest, which has less impact on the performance of the surrounding stations.